Load-bearing capacity of concrete hollow blocks containing rice husks - Uniana, Eugene T.; Mostrales, Daniel S.; Orejudos, Jerson N. (2000)
This research measures the feasibility of Rice Husks (RH) as additves in cement-aggregate mixture of a load-bearing Concrete Hollow Block (CHB). Results show that 4% of Pulverized Rice Husks (PRH) mixed with cement, and aggregates at 1:3 mix ratio, plus water, gives a compressive strength of 10.72 MPa (1,555 psi) and 11.39 MPa (1,652 psi) at age 14 and 28 days, respectively, of a load-bearing CHB in conformity with the ACI, British, and Philippine National Standards. Concrete Hollow Blocks (CHB) containing PRH result to a higher compressive strength compared to CHB's containing Unpulverized Rice Husks (URH); 1% and 2.6% by weight URH mixed with 1:3 ratio of cement and aggregates, give 8.64 MPa (1,254 psi) and 7.30 MPa (1,059 psi), respectively, at age 28 days. A mix ratio of 1:5 at 1% URH gives 7.05 MPa (1,023 psi).
Keywords: Concrete Hollow Blocks; Rice husks; Hollow blocks; Mindanao studies